Radiopacity evaluation of calcium silicate cements - Havva Gozde Sen; Dilek Helvacioglu-Yigit; Ayca Yilmaz (BMC, 2023)
Abstract Background The aim of this study was to compare the radiopacity of calcium silicate cements using a digital imaging method. Methods Four calcium silicate cements, NeoMTA 2, OrthoMTA, ProRoot MTA, and Biodentine, were used in this study. Disk-shaped samples were prepared from each material and placed on a plexiglass plate. An aluminum step-wedge was placed alongside the samples on a digital sensor and exposed to 70 kVp and 8 mA from 30 cm away for 0.32 s. The greyness values ​​of the tested materials were measured digitally with the system software and compared with those of the step-wedge to determine the equivalent aluminum thickness. Results The radiopacity values, expressed in equivalent millimetres of aluminum, of the studied materials ProRoot MTA, OrthoMTA, NeoMTA 2, and Biodentine were 4.32 ± 0.17 mm Al, 3.92 ± 0.09 mm Al, 3.83 ± 0.07 mm Al, and 2.29 ± 0.21 mm Al, respectively. Statistically significant differences were found between the mean radiographic density values of the tested materials (p < 0.05). Conclusion ProRoot MTA was the most radiopaque root canal filling material among the tested materials. All materials, except Biodentine, were found to be compliant with the minimum radiopacity requirements of ISO 6876 and ADA 57 standards.